Adhesive resin composition, cured product, and laminate

By introducing comb urethane-acrylic composite resin and liquid epoxy resin into epoxy adhesive, combined with hardener, the stress problem and hardening temperature of the adhesive when bonding between light metal and fiber reinforced plastic is solved. The physical properties difference caused by the achievement of high flexibility, impact resistance and excellent adhesiveness, is suitable for a variety of industrial fields and reduces the use of solvents.

CN119487146AActive Publication Date: 2025-02-18아티엔스가부시키가이샤 +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202380046898.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-24
Filing Date
2023-08-15
Publication Date
2025-02-18
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

When the existing epoxy adhesive bonds bond light metals and fiber reinforced plastics, the difference in expansion rate between the materials leads to high stress, which leads to easy destruction of the adhesive and large differences in physical properties caused by the hardening temperature, which affects the use effect.

Method used

Adhesive resin composition containing comb-carbamate-acrylic composite resin, liquid epoxy resin and hardener to improve the softness and impact resistance of the adhesive by combining the comb structure and liquid epoxy resin. and reduce the physical properties difference caused by hardening temperature.

Benefits of technology

It achieves high flexibility, impact resistance and excellent adhesiveness, while reducing physical properties differences caused by hardening temperature. It is suitable for automobiles, building materials, ships, aircraft and other fields, and can be used without solvents, improving environmental protection and safety. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005186347510000131
    Figure BDA0005186347510000131
  • Figure BDA0005186347510000141
    Figure BDA0005186347510000141
  • Figure BDA0005186347510000151
    Figure BDA0005186347510000151
Patent Text Reader

Abstract

The present invention addresses the problem of providing an adhesive resin composition which has high flexibility, impact resistance and adhesive strength, has little difference in physical properties due to the curing temperature, is particularly suitable for use in the fields of automobiles, building materials, ships, aircrafts and the like, and can be used without a solvent. The problem of the present invention is solved by an adhesive resin composition containing a comb-type urethane-acrylic composite resin (D), a liquid epoxy resin (E), and a curing agent (F). Wherein the comb-type urethane-acrylic composite resin (D) has residues derived from an acrylic polyol (A) containing an epoxy group in the molecule and having a hydroxyl group at a single terminal, a polyol (B) (excluding the acrylic polyol (A)), and a diisocyanate (C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive resin composition, a cured product thereof, and a laminate including the cured product. Background Art

[0002] In recent years, in the fields of automobiles and aircraft, in order to improve fuel efficiency and promote the lightweighting of vehicle bodies, the use rate of lightweight raw materials such as light metals such as aluminum and magnesium or fiber reinforced plastic materials (hereinafter referred to as FRP (fiber reinforced plastic)) has increased. In addition, in its assembly, the use of adhesives is increasing instead of welding-based joining. Among them, two-liquid curing epoxy adhesives have high adhesion and durability to various components, and the viscosity after mixing increases slowly, and the workability is also excellent, so they are widely used as structural adhesives.

[0003] However, for example, when bonding metals such as aluminum to materials with different linear expansion coefficients such as FRP, high stress is applied to the adhesive layer due to the difference in expansion coefficient between the materials caused by temperature changes during the manufacturing process or in the use temperature environment. Conventional epoxy adhesives have the problem of being easily broken by impact due to their hardness and brittleness.

[0004] To address such a problem, for example, in Patent Document 1, rubber-like polymer particles are dispersed in a curable resin composition containing epoxy resin as a main component to impart flexibility. In addition, in Patent Documents 2 to 4, relatively large amounts of high molecular weight epoxy resins or modified epoxy resins are used to solve the above problem.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-182248

[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-063595

[0009] Patent Document 3: Japanese Patent Application Publication No. 2017-002130

[0010] Patent Document 4: Japanese Patent Application Publication No. 2018-002766 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, if rubber-like polymer particles or high molecular epoxy resin components are added in order to improve the flexibility of epoxy resin composition, workability is reduced due to high viscosity, so the amount added is limited or a solvent needs to be added. That is, sufficient flexibility cannot be given in the method of adding soft components, and it is still hard and fragile and not impact-resistant. In addition, adding a solvent will increase environmental load. Therefore, improvement is required on the market. In addition, in the case of introducing a soft skeleton by modifying epoxy resin, as a disadvantage, the compatibility with other materials is deteriorated, and physical properties change greatly or processing becomes difficult due to the curing temperature.

[0013] The present invention is made in view of the above background, and its purpose is to provide an adhesive resin composition which has high flexibility, impact resistance and adhesion, and has little difference in physical properties caused by curing temperature, is particularly suitable for the fields of automobiles, building materials, ships, aircraft, etc., and can be used without solvent.

[0014] Technical means of solving problems

[0015] The present inventors have made intensive studies to solve the above-mentioned problems, and as a result, have found that the problems of the present invention can be solved by the following means, thereby completing the present invention.

[0016] [1]: An adhesive resin composition comprising: a comb-type urethane-acrylic composite resin (D) having residues derived from an acrylic polyol (A) containing an epoxy group in the molecule and having a hydroxyl group at one end, a polyol (B) (except the acrylic polyol (A)), and a diisocyanate (C); a liquid epoxy resin (E); and a hardener (F).

[0017] [2]: The adhesive resin composition according to [1], wherein the liquid epoxy resin (E) has two or more epoxy groups in the molecule.

[0018] [3]: The adhesive resin composition according to [1] or [2], wherein the acrylic polyol (A) is contained in an amount of 5 to 80% by mass in 100% by mass of the comb-type urethane-acrylic composite resin (D).

[0019] [4]: The adhesive resin composition according to any one of [1] to [3], characterized in that 100% by mass of the acrylic polyol (A) contains 5% by mass or more and less than 100% by mass of an ethylenically unsaturated monomer (a-1) having one or more epoxy groups in its molecule.

[0020] [5]: The adhesive resin composition according to any one of [1] to [4], characterized in that the liquid epoxy resin (E) is contained in an amount of 20% to 80% by mass in 100% by mass of the total of the comb-type urethane-acrylic composite resin (D) and the liquid epoxy resin (E).

[0021] [6]: A cured product comprising the adhesive resin composition according to any one of [1] to [5].

[0022] [7]: A laminate having a layer comprising the cured product according to [6] on a substrate.

[0023] Effects of the Invention

[0024] According to the present invention, an adhesive resin composition can be provided which has high flexibility, impact resistance and adhesive strength, has little difference in physical properties caused by curing temperature, is particularly suitable for the fields of automobiles, building materials, ships, aircraft, etc., and can be used without solvent. DETAILED DESCRIPTION

[0025] Hereinafter, the present invention will be described in detail. In addition, as long as it is consistent with the gist of the present invention, other embodiments are also included in the scope of the present invention. In addition, in this specification, the numerical range specified by "~" is set to include the numerical values ​​recorded before and after "~" as the range of the lower limit and the upper limit. In addition, the various components appearing in this specification can be used independently and separately as long as there is no special annotation, or two or more can be used in combination.

[0026] In the present specification, acrylic polyol (A) containing an epoxy group in the molecule and having a hydroxyl group at one terminal may be simply referred to as acrylic polyol (A), and polyol (B) (excluding acrylic polyol (A)) may be simply referred to as polyol (B).

[0027] The adhesive resin composition of the present invention contains: a comb-type urethane-acrylic composite resin (D) having residues derived from an acrylic polyol (A) containing an epoxy group in the molecule and having a hydroxyl group at one end, a polyol (B), and a diisocyanate (C); a liquid epoxy resin (E); and a hardener (F).

[0028] By incorporating an acrylic polyol (A) containing an epoxy group in the molecule and having a hydroxyl group at one end into a carbamate resin in a comb-like shape, the crosslinking of the epoxy group is formed away from the soft carbamate main chain. Therefore, compared with the linear block structure, the comb-type carbamate-acrylic composite resin (D) has excellent flexibility while maintaining strength. In addition, compared with rubber particles, it has a low molecular weight and soft skeleton, so the viscosity is low and the workability can be improved. Furthermore, by compounding the acrylic resin and the carbamate resin, the compatibility with other materials becomes good, thereby reducing the difference in physical properties caused by the difference in curing temperature.

[0029] Therefore, the adhesive resin composition of the present invention is suitable for use as a structural adhesive in the fields of automobiles, building materials, ships, aircraft, etc. In addition, the adhesive resin composition of the present invention can be used as a liquid solvent-free adhesive, which is also excellent in terms of safety and environmental compliance.

[0030] 《Comb-shaped urethane-acrylic composite resin (D)》

[0031] The comb-shaped urethane-acrylic composite resin (D) of the present invention may have a comb-shaped structure having (meth)acrylic units containing acrylic polyol (A) in the side chain and urethane units containing polyol (B) and diisocyanate (C) as the main chain, and the production method thereof is not limited. Preferably, it can be produced by the following method.

[0032] Step 1: An acrylic polyol (A) having an epoxy group in the molecule and a hydroxyl group at one end is synthesized by polymerizing an ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule and other ethylenically unsaturated monomers (a-2) using a chain transfer agent having two hydroxyl groups and a mercapto group in the molecule as a starting point.

[0033] Step 2: The hydroxyl groups in the acrylic polyol (A) and the hydroxyl groups in the polyol (B) are reacted with the isocyanate groups in the diisocyanate (C) to link the (meth)acrylic acid units and the urethane units in a comb shape.

[0034] The reactions of step 1 and step 2 may be carried out using a solvent or without a solvent. In addition, a part or all of the solvent may be replaced with a liquid epoxy resin (E). In this case, the liquid epoxy resin (E) functions as a reactive diluent.

[0035] When a solvent is used in step 1 or step 2, the solvent can be removed under reduced pressure or normal pressure in the middle of the reaction or after the reaction is completed, thereby obtaining a solvent-free comb-type urethane-acrylic composite resin (D).

[0036] The reactive diluent in the present invention is defined as a substance used to dilute the concentration of substances in the reaction system and the viscosity of the reaction liquid to an appropriate range, and is a substance that participates in the curing reaction and does not evaporate in the process of manufacturing the adhesive resin composition and curing it into a cured product. On the other hand, the so-called solvent is defined as a substance that has the function of diluting the concentration of substances in the reaction system and the viscosity of the reaction liquid to an appropriate range, but evaporates and is removed by distillation or drying in any process of manufacturing the adhesive resin composition and curing it into a cured product.

[0037] The reaction in step 2 is carried out using a conventional urethanization reaction, and a catalyst may be used for the purpose of adjusting the reactivity.

[0038] <Catalyst>

[0039] As the catalyst, existing metal catalysts, amine catalysts, etc. can be used. As metal catalysts, dibutyltin dilaurate, tin octoate, dibutyltin di(2-ethylhexanoate), lead 2-ethylhexanoate, 2-ethylhexanoate, titanium ethyl acetate, 2-ethylhexanoate iron, 2-ethylhexanoate cobalt, zinc naphthenate, cobalt naphthenate, tetra-n-butyltin, etc. can be listed. As amine catalysts, tertiary amines such as tetramethylbutylene diamine can be listed. The amount of the catalyst used is based on the total mass of acrylic polyol (A) and polyol (B), preferably in the range of 0.01 to 0.05 parts by mass.

[0040] The number average molecular weight of the comb-type urethane-acrylic composite resin (D) is not particularly limited, but is preferably 5,000 to 100,000. When it is 5,000 or more, the cohesive force is good, so the adhesive force is excellent, and when it is 100,000 or less, the viscosity is low, so the viscosity adjustment without a solvent is easy.

[0041] <Acrylic polyol (A)>

[0042] The acrylic polyol (A) contains an epoxy group in the molecule and has a hydroxyl group at one terminal so as to be linked in a comb-like manner to the urethane unit containing the polyol (B) and the diisocyanate (C).

[0043] The method for producing the acrylic polyol (A) is not particularly limited as long as a hydroxyl group can be introduced at one end, and for example, a conventional polymerization method using a radical polymerization initiator having a hydroxyl group, a living radical polymerization initiator, a chain transfer agent, etc. can be used.

[0044] The method for producing acrylic polyol (A) can use the existing method, but the method of polymerizing the ethylenically unsaturated monomer (a-1) containing one or more epoxy groups in the molecule in the presence of a chain transfer agent having two hydroxyl groups and one mercapto group in the molecule is simple and preferred. In addition, in order to adjust the compatibility and cohesive force, other ethylenically unsaturated monomers (a-2) may be included in addition to the ethylenically unsaturated monomer (a-1) containing one or more epoxy groups in the molecule.

[0045] <Ethylenically unsaturated monomers having one or more epoxy groups in the molecule (a-1)>

[0046] As the ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule, it is not limited to the following examples, and compounds having one polymerizable unsaturated double bond and one or more epoxy groups in the molecule can be used, for example, glycidyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, 4,5-epoxypentyl (meth)acrylate, 6,7-epoxypentyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, lactone-modified 3,4-epoxycyclohexyl (meth)acrylate, vinylcyclohexene oxide, etc. can be mentioned.

[0047] <Other ethylenically unsaturated monomers (a-2)>

[0048] The other ethylenically unsaturated monomers (a-2) are not limited to the following examples, and examples thereof include: linear or branched alkyl ethylenically unsaturated monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cetyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate;

[0049] Cyclic alkyl (meth)acrylates such as cyclohexyl (meth)acrylate, tert-butyl cyclohexyl (meth)acrylate, dicyclopentane (meth)acrylate, dicyclopentaneoxyethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and isobornyl (meth)acrylate;

[0050] Fluoroalkyl ethylenically unsaturated monomers such as trifluoroethyl (meth)acrylate, octafluoropentyl (meth)acrylate, perfluorooctylethyl (meth)acrylate, and tetrafluoropropyl (meth)acrylate;

[0051] Ethylenically unsaturated monomers having a heterocyclic ring, such as tetrahydrofurfuryl (meth)acrylate and 3-methyl-3-oxetanyl (meth)acrylate;

[0052] (Meth)acrylates having an aromatic ring, such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, p-cumylphenoxypolyethylene glycol (meth)acrylate, or nonylphenoxypolyethylene glycol (meth)acrylate; methoxypolyethylene glycol mono(meth)acrylate, octyloxypolyethylene glycol polypropylene glycol mono(meth)acrylate, lauryloxypolyethylene glycol mono(meth)acrylate, stearyloxypolyethylene glycol mono(meth)acrylate, phenoxypolyethylene glycol mono(meth)acrylate, phenoxypolyethylene glycol polypropylene glycol mono(meth)acrylate Ethylenically unsaturated monomers having an alkyl ether group, such as ethylenic ...

[0053] Ethylenically unsaturated monomers having an oxetane group, such as 3-(acryloyloxymethyl)3-methyloxetane, 3-(methacryloyloxymethyl)3-methyloxetane, 3-(acryloyloxymethyl)3-ethyloxetane, 3-(methacryloyloxymethyl)3-ethyloxetane, 3-(acryloyloxymethyl)3-butyloxetane, 3-(methacryloyloxymethyl)3-butyloxetane, 3-(acryloyloxymethyl)3-hexyloxetane, and 3-(methacryloyloxymethyl)3-hexyloxetane;

[0054] Ethylenically unsaturated monomers having a vinyl group, such as styrene, α-methylstyrene, vinyl acetate, vinyl (meth)acrylate, or allyl (meth)acrylate;

[0055] Ethylenically unsaturated monomers having an ether group, such as ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, or isobutyl vinyl ether;

[0056] (Meth) acrylonitrile, cyanostyrene, cyanoacrylate and other ethylene unsaturated monomers containing cyano groups;

[0057] Ethylenically unsaturated monomers having a keto group, such as acrolein, methacrolein, diacetone acrylamide, diacetone methacrylamide, vinyl methyl ketone, vinyl ethyl ketone, and formylstyrol.

[0058] The content of the ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule is preferably 5% by mass or more and less than 100% by mass in the total 100% by mass of the ethylenically unsaturated monomers constituting the acrylic polyol (A).

[0059] Furthermore, when the acrylic polyol (A) is produced by a method of polymerizing an ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule in the presence of a chain transfer agent having two hydroxyl groups and one mercapto group in the molecule, the monomer (a-1) is preferably 5% by mass or more and less than 100% by mass, and more preferably 10% by mass or more and 70% by mass or less. When the content of the ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule is 5% by mass or more and less than 100% by mass, the ethylenically unsaturated monomer (a-1) is sufficiently incorporated into a strong cross-linked structure comprising the liquid epoxy resin (E) and the hardener (F) by curing, so that a cross-linked structure having excellent adhesiveness and flexibility can be formed.

[0060] <Chain transfer agent>

[0061] The chain transfer agent is not particularly limited as long as it is a compound having a functional group that can react with an isocyanate group and a mercapto group in the molecule, but preferably a compound having two hydroxyl groups and one mercapto group in the molecule. By forming the mercapto group as a chain transfer agent, an acrylic polyol (A) having a hydroxyl group at one end can be efficiently synthesized.

[0062] The compound having two hydroxyl groups and one mercapto group in the molecule is not particularly limited, and examples thereof include 1-mercapto-1,1-methanediol, 1-mercapto-1,1-ethylenediol, 3-mercapto-1,2-propylene glycol (thioglycerin or 1-thioglycerol), 2-mercapto-1,2-propylene glycol, 2-mercapto-2-methyl-1,3-propylene glycol, 2-mercapto-2-ethyl-1,3-propylene glycol, 1-mercapto-2,2-propylene glycol, 2-mercaptoethyl-2-methyl-1,3-propylene glycol, or 2-mercaptoethyl-2-ethyl-1,3-propylene glycol. Among these, 3-mercapto-1,2-propylene glycol is preferred because of its good reactivity and simple synthesis.

[0063] <Polymerization initiator>

[0064] As the polymerization initiator, an existing azo compound or organic peroxide can be used. The azo compound is not limited to the following examples, and examples thereof include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), dimethyl 1,1'-azobis(1-cyclohexanecarboxylate), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), or 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. The organic peroxide is not limited to the following examples, and examples thereof include benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0065] The polymerization initiator is preferably used in an amount of 0.001% by mass to 15% by mass based on the total mass of the acrylic polyol (A). A range of 0.001% by mass to 15% by mass is more preferred because chain transfer polymerization proceeds effectively.

[0066] The comb-type urethane-acrylic composite resin (D) preferably contains 5% to 80% by mass of the acrylic polyol (A) in the total mass (100% by mass), and more preferably 15% to 60% by mass. When 5% to 80% by mass is contained, a sufficient cross-linked structure can be formed at a site away from the urethane main chain having excellent flexibility, so that flexibility and breaking strength are excellent, and compatibility becomes good, thereby suppressing phase separation during curing.

[0067] The number average molecular weight of the acrylic polyol (A) is not particularly limited, but is preferably 1,000 to 10,000.

[0068] <Polyol (B)>

[0069] The polyol (B) is a compound having two or more hydroxyl groups in the molecule other than the acrylic polyol (A), and typical examples of the polyol include polyether polyol, polyester polyol, polycarbonate polyol, polyolefin polyol, and plant-derived polyol.

[0070] Furthermore, examples of the compound having two or more hydroxyl groups in the molecule include polyols obtained by using a compound having at least two active hydroxyl groups such as a low molecular weight polyol, aliphatic amine compounds, aromatic amine compounds, alkanolamines or bisphenols as a starting material, and adding an alkylene oxide such as methylene oxide, ethylene oxide, propylene oxide, tetrahydrofuran or polyoxytetramethylene oxide thereto.

[0071] Examples of the low molecular weight polyol include bifunctional low molecular weight polyols and trifunctional or higher functional low molecular weight polyols.

[0072] The difunctional low molecular weight polyol is not particularly limited, and examples thereof include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, neopentyl glycol, pentanediol, hexanediol, octanediol, nonanediol, dipropylene glycol, diethylene glycol, triethylene glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, polyoxyethylene glycol (addition mole number is 10 or less), polyoxypropylene glycol (addition mole number is 10 or less), cyclohexanediol, cyclohexanedimethanol, tricyclodecane dimethanol, cyclopentadienyl dimerol, and dimer alcohol. diol), bisphenol A, N,N-bis(2-hydroxypropyl)aniline, dihydroxymethylacetic acid, dihydroxymethylpropionic acid, dihydroxymethylbutyric acid, 2,2-dihydroxymethylbutyric acid, 2,2-dihydroxymethylvaleric acid, dihydroxysuccinic acid, dihydroxypropionic acid, dihydroxybenzoic acid.

[0073] The trifunctional or higher low molecular weight polyol is not particularly limited, and examples thereof include trimethylolethane, trimethylolpropane, 1,1,1-trimethylolbutane, 1,2,3-butanetriol, 1,2,4-butanetriol, 1,2,6-butanetriol, trimethylolbutene, trimethylolpentene, trimethylolhexene, trimethylolheptene, trimethyloloctene, trimethylolnonene, trimethyloldecene, trimethylolundecene, trimethyloldodecene, trimethyloltridecene, trimethylolpentadecene, trimethylolhexadecene, trimethylolhexadecene, trimethylolpentadecene ... 1,2,3-octantriol, 1,3,7-octantriol, 3,7-dimethyl-1,2,3-octantriol, 1,1,1-1,1,1-trimethyloldecane, 1,2,10-decanetriol, 1,1,1-trimethylol-2-methyl-hexane, 1,1,1-trimethylol-3-methyl-hexane, 1,1,1-trimethylol-2-ethyl-hexane, 1,1,1-trimethylol-3-ethyl-hexane, trimethylolhexene, 1,2,3-octantriol, 1,3,7-octantriol, 3,7-dimethyl-1,2,3-octantriol, 1,1,1-1,1,1-trimethyloldecane, 1,2,10-decanetriol, 1,1, 1-Trihydroxymethylisoheptadecane, 1,1,1-trihydroxymethyl-sec-butane, 1,1,1-trihydroxymethyl-tert-pentane, 1,1,1-trihydroxymethyl-tert-nonane, 1,1,1-trihydroxymethyl-tert-tridecane, 1,1,1-trihydroxymethyl-tert-heptadecane, 1,1,1-trihydroxymethyl-2-methyl-hexane, 1,1,1-trihydroxymethyl-3-methyl-hexane, 1,1,1-trihydroxymethyl-2-ethyl-hexane, 1,1,1-trihydroxymethyl-3-ethyl-hexane, 1,1,1-trihydroxymethyl isoheptadecane, 1,2,3,4-butanetetrol, pentaerythritol, dipentaerythritol, tripentaerythritol, glycerol, diglycerol, triglycerol, polyglycerol, di-trimethylolethane, di-trimethylolpropane, tris(2-hydroxyethyl)isocyanurate, benzene-1,3,5-triol, benzene-1,2,3-triol, stilbene-3,4',5-triol, sucrose, inositol, sorbitan, sorbitol, mannitol, saccharose, cellulose, and xylitol.

[0074] Examples of aliphatic amine compounds include ethylenediamine, triethylenetetramine, diethylenetriamine, and triaminopropane. Examples of aromatic amine compounds include toluenediamine and diphenylmethane-4,4-diamine. Examples of alkanolamines include ethanolamine and diethanolamine. Examples of bisphenols include bisphenol A, bisphenol AP, bisphenol B, bisphenol C, bisphenol E, and bisphenol F.

[0075] Examples of the polyether polyol include diols such as polyethylene glycol, polypropylene glycol, and poly(ethylene / propylene) glycol, which are polymers or copolymers of methylene oxide, ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, etc. In addition, examples include polyether polyols obtained by condensation of hexanediol, methyl hexanediol, heptanediol, octanediol, or a mixture thereof.

[0076] Examples of the polyester polyol include polyester polyols obtained by condensation reaction of the above-mentioned low molecular weight polyols and a dibasic acid component.

[0077] Examples of the dibasic acid component include aliphatic or aromatic dibasic acids such as terephthalic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, hydrogenated dimer acid, phthalic anhydride, isophthalic acid, trimellitic acid, glutaric acid, pimelic acid, suberic acid, and sebacic acid, and anhydrides thereof.

[0078] In addition, polyester polyols obtained by ring-opening polymerization of cyclic ester compounds such as lactones such as ε-caprolactone, poly(β-methyl-γ-valerolactone) and polyvalerolactone can be mentioned.

[0079] Examples of the polycarbonate polyol include reaction products obtained by reacting the above-mentioned low molecular weight polyol with a carbonate compound such as a dialkyl carbonate, an alkylene carbonate, or a diaryl carbonate.

[0080] Examples of the dialkyl carbonate include dimethyl carbonate and diethyl carbonate, examples of the alkylene carbonate include ethylene carbonate, and examples of the diaryl carbonate include diphenyl carbonate.

[0081] Examples of the polyolefin polyol include hydroxyl-containing polybutadiene, hydrogenated hydroxyl-containing polybutadiene, hydroxyl-containing polyisoprene, hydrogenated hydroxyl-containing polyisoprene, hydroxyl-containing chlorinated polypropylene, and hydroxyl-containing chlorinated polyethylene.

[0082] Examples of the vegetable oil-based polyol include polyols produced from plant-derived castor oil, dimer acid, or soybean oil as a raw material.

[0083] Among these, polyether polyol, polyester polyol and polycarbonate polyol are preferred. Polyether polyol and polycarbonate polyol are more preferred because they are excellent in flexibility.

[0084] The polyester polyol, polycarbonate polyol, polyolefin polyol, and vegetable oil polyol preferably have a number average molecular weight of 500 to 5,000, more preferably 700 to 3,500. A number average molecular weight of 500 to 5,000 is preferred because the obtained cured product has better adhesion and flexibility.

[0085] Furthermore, the polyol (B) may be used in combination with the above-mentioned low-molecular-weight polyol for the purpose of adjusting the urethane bond concentration or introducing various functional groups within a range not impairing the effects of the present invention.

[0086] <Diisocyanate (C)>

[0087] The diisocyanate (C) constituting the urethane unit may be any compound having two isocyanate groups in the molecule, and examples thereof include aromatic, aliphatic, and alicyclic diisocyanates.

[0088] Examples of the aromatic diisocyanate include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4′-diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2′-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, tolidine diisocyanate, xylylene diisocyanate, m-tetramethylxylene diisocyanate, p-tetramethylxylene diisocyanate, 3,3′-dimethyl-4,4′-biphenyl diisocyanate, 3,3′-dimethoxy-4,4′-biphenyl diisocyanate, 3,3′-dichloro-4,4′-biphenyl diisocyanate, and 1,5-tetrahydronaphthalene diisocyanate.

[0089] Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, lysine ester triisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, and trimethylhexamethylene diisocyanate.

[0090] Examples of the alicyclic diisocyanate include isophorone diisocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanate methyl)cyclohexane, hydrogenated xylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate.

[0091] 《Liquid epoxy resin (E)》

[0092] The liquid epoxy resin (E) of the present invention exhibits excellent adhesive strength by being incorporated into the cross-linked structure during curing. When the liquid epoxy resin (E) is used as a reactive diluent in the production process 1 and the production process 2 of the comb-type urethane-acrylic composite resin (D), synthesis without a solvent can be performed. In addition, it becomes a reactive component after the adhesive resin composition is produced.

[0093] As the liquid epoxy resin (E), there is no particular limitation as long as it is a compound that is liquid at room temperature, and preferably has two or more epoxy groups in the molecule. In addition, the epoxy equivalent is preferably 200 g / eq or less, and more preferably 150 g / eq to 200 g / eq. The epoxy equivalent of the liquid epoxy resin (E) can be determined by measuring in accordance with Japanese Industrial Standards (JIS) K-7236.

[0094] Examples of the liquid epoxy resin (E) include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol AF epoxy resin, naphthalene epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, phenol novolac epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane epoxy resin, cyclohexanedimethanol epoxy resin, glycidyl amine epoxy resin, and epoxy resin having a butadiene structure. Among these, bisphenol A epoxy resin is more preferred in terms of easy availability, good viscosity and good adhesive strength.

[0095] Regarding the adhesive resin composition of the present invention, in the total 100 mass % of the comb-type urethane-acrylic composite resin (D) and the liquid epoxy resin (E), it is preferred to include 20 mass % to 80 mass % of the liquid epoxy resin (E), and more preferably 30 mass % to 70 mass %. When the liquid epoxy resin (E) is included in an amount of 20 mass % or more, the cured product of the adhesive resin composition forms a strong cross-linked structure, thereby improving the fracture strength, and furthermore, high adhesion accompanied by high cohesion can be exhibited. In addition, since the liquid epoxy resin (E) is low in viscosity, it is easy to adjust the viscosity. On the other hand, when the content of the liquid epoxy resin (E) is 80 mass % or less, the proportion of the comb-type urethane-acrylic composite resin (D) in the adhesive resin composition is high, and the high flexibility caused by the comb-type urethane-acrylic composite resin (D) can be exhibited.

[0096] 《Hardener (F)》

[0097] The curing agent (F) is not particularly limited, and existing curing agents that cure epoxy resins can be used. For example, amine compounds, amide compounds, urea compounds, acid anhydrides, and phenolic resins can be mentioned. In order to adjust the curing speed or amine value, two or more types can be used in combination.

[0098] Examples of the amine compound include aliphatic amines such as ethylenediamine, diaminopropane, diaminobutane, diaminohexane, 2,5-dimethylhexamethylenediamine, trimethylhexamethylenediamine, diethylenetriamine, iminobispropylamine, bis(hexamethylene)triamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, N-hydroxyethylethylenediamine, and dimer esters of tetra(hydroxyethyl)ethylenediamine polyethyleneimine;

[0099] Alicyclic amines such as isophorone diamine, metacendiamine, N-aminoethylpiperazine, bis(4-amino-3-methyldicyclohexyl)methane, bis(aminomethyl)cyclohexane, 3,9-bis(3-aminopropyl)2,4,8,10-tetraoxaspiro(5,5)undecane, norbornene diamine, bis(aminomethyl)norbornene, and bis(4-aminocyclohexyl)methane;

[0100] Tetrachloro-p-xylylenediamine, m-xylylenediamine, p-xylylenediamine, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, 2,4-diaminoanisole, 2,4-toluenediamine, 2,4-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 4,4'-diamino-1,2-diphenylethane, 2,4-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, m-aminophenol, m-aminobenzylamine, benzyldimethylamine, 2-dimethylaminomethyl)phenol, triethanolamine, methylbenzylamine, Aromatic amines such as α-(m-aminophenyl)ethylamine, α-(p-aminophenyl)ethylamine, diaminodiethyldimethyldiphenylmethane, α,α'-bis(4-aminophenyl)-p-diisopropylbenzene, 3,3'-diisopropyl-4,4'-diaminodiphenylmethane, 3,3'-di-tert-butyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane, N,N-dimethylaniline, N,N-dimethylbenzylamine, and 2,4,6-tris(dimethylaminomethyl)phenol;

[0101] Imidazole derivatives such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 2,4-diethylimidazole, and 2-phenyl-4-methyl-5-hydroxyimidazole;

[0102] Boron trifluoride-amine complexes such as boron trifluoride-monoethylamine, boron trifluoride-piperidine, boron trifluoride-triethylamine, and boron trifluoride-aniline complexes;

[0103] Guanidine derivatives such as dicyandiamide, methylguanidine, ethylguanidine, propylguanidine, butylguanidine, dimethylguanidine, trimethylguanidine, phenylguanidine, diphenylguanidine, toluoylguanidine, 2,3-guanylurea, benzoyldicyandiamide, 2,6-xylylbiguanidine, and phenylbiguanidine;

[0104] Polyether polyamines such as triethylene glycol diamine, tetraethylene glycol diamine, diethylene glycol bis(propylamine), poly(propylene glycol) diamine, poly(propylene glycol) triamine, poly(ethylene glycol) diamine, poly(ethylene glycol) triamine, poly(tetramethylene ether glycol) diamine, poly(tetramethylene ether glycol) triamine, poly(propylene glycol / ethylene glycol) diamine, and poly(propylene glycol / ethylene glycol) triamine;

[0105] Polyolefin compounds having an amino group such as amine-modified polypropylene, amine-modified polyethylene, amine-modified polybutadiene, and amine-modified butadiene acrylonitrile copolymer.

[0106] Examples of the amide compound include polyamide amines having a primary amine and a secondary amine in a molecule obtained by reacting a dimer (dimer acid) of linolenic acid or oleic acid with a polyamine such as diethylenetriamine or triethylenetetramine.

[0107] The urea compound is not particularly limited as long as it has an amino group and a urea group in its molecular structure, and can be obtained, for example, by reacting the amine compound with a diisocyanate or an isocyanate-terminated prepolymer under conditions where the amino group is excessive. The isocyanate-terminated prepolymer can be obtained, for example, by reacting the polyol with a diisocyanate under conditions where the isocyanate group is excessive relative to the hydroxyl group of the polyol.

[0108] Examples of the acid anhydride include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.

[0109] Examples of the phenol resin include phenol novolac resins, cresol novolac resins, aromatic hydrocarbon formaldehyde resin-modified phenol resins, dicyclopentadiene phenol addition type resins, phenol aralkyl resins (Zylock resins), polyphenol novolac resins synthesized from polyhydroxy compounds and formaldehyde represented by resorcinol novolac resins, naphthol aralkyl resins, trimethylolmethane resins, tetraphenol ethane resins, naphthol novolac resins, naphthol-phenol co-condensation novolac resins, and naphthol. -cresol co-condensation phenolic varnish resin, biphenyl modified phenol resin (a polyphenol compound formed by linking a phenol core with a dimethylene group), biphenyl modified naphthol resin (a polyphenol compound formed by linking a phenol core with a dimethylene group), aminotriazine modified phenol resin (a polyphenol compound formed by linking a phenol core with a melamine, benzoguanamine, etc.), alkoxy-containing aromatic ring modified phenolic varnish resin (a polyphenol compound formed by linking a phenol core and an alkoxy-containing aromatic ring with formaldehyde) and the like.

[0110] Among these, amine compounds, amide compounds, and urea compounds are preferred in terms of easy adjustment of the usable time and the curing speed. As amine compounds, polyether polyamines are preferred in terms of adhesion. When polyether polyamines and urea compounds or polyolefin compounds having amino groups are used in combination, the impact resistance is excellent, so it is further preferred. The amine value of the hardener (F) is preferably 20 mgKOH / g to 800 mgKOH / g, and more preferably 180 mgKOH / g to 600 mgKOH / g. When the amine value is in the range of 20 mgKOH / g to 800 mgKOH / g, the curing reaction is fully carried out to form a good crosslinking density, so that excellent adhesion and flexibility can be exhibited. In addition, the amine value can be obtained by measuring in accordance with JIS K-7237.

[0111] The ratio of the total number of moles of all epoxy groups contained in the adhesive resin composition to the total number of moles of active hydrogen groups in the curing agent (F) participating in the reaction with the epoxy groups (epoxy groups / active hydrogen groups in the curing agent) is preferably in the range of 0.5 to 2.0, and more preferably in the range of 0.6 to 1.5. When it is in the range of 0.5 to 2.0, no unreacted functional groups remain, a good crosslinking density is formed, and thus excellent adhesive strength and flexibility can be exhibited.

[0112] 《Adhesive resin composition》

[0113] The adhesive resin composition of the present invention is obtained by mixing a comb-type urethane-acrylic composite resin (D), a liquid epoxy resin (E), and a hardener (F) by a conventional method. In addition, conventional additives such as a hardening accelerator, a silane coupling agent, a leveling agent or a defoaming agent, a filler, a propellant, a plasticizer, a superplasticizer, a wetting agent, a flame retardant, a viscosity modifier, a preservative, a stabilizer, and a colorant can be used. Such additives are preferably the following compounds, but are not limited to these compounds.

[0114] Examples of the curing accelerator include tertiary amines and salts thereof, imidazoles and salts thereof, urea compounds, phosphorus compounds, organic phosphine compounds and salts thereof, metal salts such as zinc octylate and tin octylate, compounds having a hydroxyl group such as phenols or alcohols, Lewis acids, and amine complex salts.

[0115] The amount of the curing accelerator added is preferably 0.01% by mass to 10% by mass relative to the total mass of the comb-type urethane-acrylic composite resin (D) in the adhesive resin composition.

[0116] Examples of the silane coupling agent include trialkoxysilanes having a vinyl group, such as vinyltrimethoxysilane and vinyltriethoxysilane; trialkoxysilanes having an amino group, such as 3-aminopropyltriethoxysilane and N-(2-aminoethyl)3-aminopropyltrimethoxysilane; trialkoxysilanes having a glycidyl group, such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane; trialkoxysilanes having an isocyanate group, such as 3-isocyanatepropyltriethoxysilane; and trialkoxysilanes having a mercapto group, such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane.

[0117] The amount of the silane coupling agent added is preferably 0.05% by mass to 10% by mass based on the total mass of the comb-type urethane-acrylic composite resin (D).

[0118] Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane, aralkyl-modified polymethylalkylsiloxane, polyester-modified hydroxyl-containing polydimethylsiloxane, polyether-ester-modified hydroxyl-containing polydimethylsiloxane, acrylic copolymers, methacrylic copolymers, polyether-modified polymethylalkylsiloxane, alkyl acrylate copolymers, alkyl methacrylate copolymers, and lecithin.

[0119] Examples of the defoaming agent include conventional defoaming agents such as silicone resins, silicone solutions, and copolymers of alkyl vinyl ethers, alkyl acrylates, and alkyl methacrylates.

[0120] Hardened

[0121] The cured product of the present invention is obtained by curing the adhesive resin composition, and can be obtained by mixing the comb-type urethane-acrylic composite resin (D), liquid epoxy resin (E), curing agent (F), and other components using a conventional method and curing them at 20°C to 200°C.

[0122] Layered

[0123] The laminate of the present invention has a layer containing the cured product on a substrate. The laminate can be formed using an existing lamination method. For example, an adhesive composition is applied to one surface of a substrate to form an adhesive layer, and then another substrate is overlapped on the adhesive layer before the curing treatment, and the adhesive layer is cured under the condition of 20°C to 200°C, thereby obtaining a laminate having a substrate and a layer containing a cured product of the adhesive resin composition.

[0124] The substrate used for the laminate is not particularly limited. Suitable substrates include, for example, metals such as stainless steel, thermoplastic polymers such as polyethylene, polypropylene, polyurethane, polyacrylate, polycarbonate and copolymers thereof, thermosetting polymers such as vulcanized rubber, urea-formaldehyde foam, melamine resin, wood, carbon fiber reinforced plastics, glass fiber reinforced plastics and other fiber reinforced plastics.

[0125] The adhesive resin composition of the present invention can be used for bonding various substrates. The substrates to be bonded can be the same or different. The film thickness of the adhesive resin composition is preferably 0.1 μm to 300 mm.

[0126] The adhesive resin composition of the present invention has excellent flexibility and adhesive strength, and a laminate using the adhesive resin composition is effectively used as structural members (panel parts, frame parts, axle parts, etc.) of transportation equipment such as automobiles, building materials, ships, and aircraft.

[0127] Example

[0128] Hereinafter, the present invention will be described in more detail by way of examples, but the following examples do not impose any limitation on the scope of the present invention. In addition, unless otherwise specified, "parts" in the examples represent "parts by mass" and "%" represents "% by mass".

[0129] <Number average molecular weight>

[0130] The number average molecular weight of acrylic polyol (A) and urethane-acrylic composite resin (D) was calculated by gel permeation chromatography (GPC) as a conversion value based on standard polystyrene. The measurement was carried out under the conditions of a flow rate of 0.6 mL / min, an injection volume of 10 μL, and a column temperature of 40°C using GPC-8020 (manufactured by Tosoh Corporation) as a GPC apparatus, tetrahydrofuran as an eluent, and three TSK gelSuper HM-M (manufactured by Tosoh Corporation) connected in series as a column. In addition, the number average molecular weight of the urea compound and the polyolefin compound was calculated similarly using ACQUITY UPLC (Ultra Performance Liquid Chromatography) (manufactured by Waters Corporation), 3 mM triethylamine and 10 mM LiBr in N,N-dimethylformamide solution as eluent, three TSK gel Super HM-M (manufactured by Tosoh Corporation) connected in series as a column, and the calculation was carried out under the conditions of a flow rate of 0.6 mL / min, an injection volume of 10 μL, and a column temperature of 40°C.

[0131] The abbreviations of the compounds in this specification are shown below.

[0132] <Ethylenically unsaturated monomers containing one or more epoxy groups in the molecule (a-1)>

[0133] ·GMA: Glycidyl Methacrylate

[0134] <Other ethylenically unsaturated monomers (a-2)>

[0135] ·BMA: n-butyl methacrylate

[0136] ·MMA: Methyl (meth)acrylate

[0137] <Polyol (B)>

[0138] · P-2000: Difunctional polypropylene glycol, number average molecular weight 2,000, manufactured by ADEKA

[0139] ·C-1090: Difunctional polycarbonate polyol, number average molecular weight 1,000, manufactured by Kuraray

[0140] <Diisocyanate (C)>

[0141] IPDI: Isophorone diisocyanate

[0142] ·MDI: diphenylmethane diisocyanate

[0143] <Liquid epoxy resin (E)>

[0144] ·jER828: Bisphenol A epoxy resin, epoxy equivalent 190g / eq, manufactured by Mitsubishi Chemical Corporation

[0145] ·EX-141: Phenyl glycidyl ether, epoxy equivalent 151 g / eq, manufactured by Nagase ChemteX

[0146] <Hardener (F)>

[0147] D-400: polyoxypropylene diamine, weight average molecular weight 430, amine value 520 mgKOH / g, manufactured by Huntsman

[0148] ·EH-4024W: Polyamide amine resin, amine value 200 mgKOH / g, manufactured by ADEKA

[0149] D-2000: polyoxypropylene diamine, weight average molecular weight 2000, amine value 56.1 mgKOH / g, manufactured by Huntsman

[0150] Krasol LBH-P3000: terminal hydroxyl-modified liquid polybutadiene, weight average molecular weight 3000, manufactured by Crayvalley

[0151] (Production Example 1)

[0152] In a reaction vessel equipped with a nitrogen inlet pipe, a stirrer, a thermometer and a reflux device, 1.15 parts of 1-thioglycerol as a chain transfer agent having a mercapto group, 1.6 parts of glycidyl methacrylate as an ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule, 29.0 parts of n-butyl methacrylate as another ethylenically unsaturated monomer (a-2), and 50% by weight of methyl ethyl ketone based on the total weight of the ethylenically unsaturated monomers were first added, and the temperature was raised to 75° C. under a nitrogen atmosphere. 2,2′-azobis(2′4-dimethylvaleronitrile) as a polymerization initiator was added thereto seven times at 1 hour intervals. After the addition of the polymerization initiator, the reaction was continued for 2 hours to obtain an acrylic polyol (A-1). Next, 5.1 parts of P-2000 as polyol (B), 2.9 parts of isophorone diisocyanate as diisocyanate (C), and 0.01% of butyltin dilaurate as catalyst were added to the total mass of acrylic polyol (A-1), polyol (B) and diisocyanate (C), and the mixture was stirred uniformly. Then, 60 parts of jER828 as liquid epoxy resin (E) was added under nitrogen atmosphere at 90°C for half a day for 4 hours, and the mixture was stirred uniformly. Then, methyl ethyl ketone was removed under reduced pressure to obtain a composition (DE-1) containing a comb-type urethane-acrylic composite resin (D-1) and a liquid epoxy resin (E-1). The end point of the reaction was determined by the peak (2270 cm) derived from the isocyanate group by FT-IR (Fourier Transform infrared spectroscopy). -1 The number average molecular weights of the obtained acrylic polyol (A-1) and comb-type urethane-acrylic composite resin (D-1), the ratio (%) of acrylic moieties in the comb-type urethane-acrylic composite resin (D-1), the ratio (%) of monomers having epoxy groups in the acrylic polyol (A-1), and the ratio (%) of the liquid epoxy resin (E-1) relative to the total mass of the comb-type urethane-acrylic composite resin (D-1) and the liquid epoxy resin (E-1) are shown in Table 1.

[0153] (Manufacturing Example 2 to Manufacturing Example 26)

[0154] The same operation as in Preparation Example 1 was carried out except that the compounds and formulation compositions shown in Tables 1 to 3 were changed to obtain compositions (DE-2 to DE-26) containing a comb-type urethane-acrylic composite resin (D) and a liquid epoxy resin (E) of Preparation Examples 2 to 26. The number average molecular weights of the obtained acrylic polyol (A) and the comb-type urethane-acrylic composite resin (D), the ratio (%) of the acrylic moiety in the comb-type urethane-acrylic composite resin (D), the ratio (%) of the monomer having an epoxy group in the acrylic polyol (A), and the ratio (%) of the liquid epoxy resin (E) to the total mass of the comb-type urethane-acrylic composite resin (D) and the liquid epoxy resin (E) are shown in Tables 1 to 3.

[0155]

[0156]

[0157]

[0158] (Comparative Manufacturing Example 1)

[0159] The same operation as in Production Example 1 was performed except that the compounds and formulations shown in Table 4 were used instead, thereby obtaining a composition (U-1) containing a comb-type urethane-acrylic composite resin and a liquid epoxy resin. The number average molecular weights of the obtained acrylic polyol and the comb-type urethane-acrylic composite resin, the ratio (%) of the acrylic moiety in the comb-type urethane-acrylic composite resin, the ratio (%) of the monomer having an epoxy group in the acrylic polyol, and the ratio (%) of the liquid epoxy resin to the total mass of the comb-type urethane-acrylic composite resin and the liquid epoxy resin are shown in Table 3.

[0160] (Comparative Manufacturing Example 2)

[0161] In a reaction vessel equipped with a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device, 1.4 parts of 1-thioglycerol as a chain transfer agent having a mercapto group, 4.0 parts of glycidyl methacrylate as an ethylenically unsaturated monomer having one or more epoxy groups in the molecule, 34.3 parts of n-butyl methacrylate as another ethylenically unsaturated monomer, and 50% of methyl ethyl ketone based on the total mass of the chain transfer agent and the ethylenically unsaturated monomer were first added, and the temperature was raised to 75° C. in a nitrogen atmosphere, and 0.7% of 2,2'-azobis(2'4-dimethylvaleronitrile) as a polymerization initiator was added thereto every 1 hour for seven times, and the reaction was continued for another 2 hours after the addition of the polymerization initiator to obtain an acrylic polyol. Subsequently, 60 parts of jER828 as a liquid epoxy resin was added, and after uniform stirring, the methyl ethyl ketone was removed under reduced pressure to obtain a composition (U-2) containing an acrylic polyol and a liquid epoxy resin. The number average molecular weight of the obtained acrylic polyol, the proportion of acrylic polyol in acrylic resin (%), the proportion of monomers having epoxy groups in acrylic polyol (%), and the proportion of liquid epoxy resin relative to the total mass of acrylic polyol and liquid epoxy resin (%) are shown in Table 3.

[0162] (Comparative Production Example 3)

[0163] In a reaction vessel including a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device, 36.8 parts of P-2000 as a polyol, 3.2 parts of isophorone diisocyanate as a diisocyanate, 0.01% of butyltin dilaurate as a catalyst relative to the total mass of the polyol and the diisocyanate, and 50% of methyl ethyl ketone relative to the total mass of the monomers were first charged, and after uniform stirring, 60 parts of jER828 as a liquid epoxy resin was added at 90° C. for 30 minutes under a nitrogen atmosphere, and after uniform stirring, the methyl ethyl ketone was removed under reduced pressure to obtain a composition (U-3) containing a urethane resin and a liquid epoxy resin. The end point of the reaction was determined by the peak derived from the isocyanate group (2270 cm -1 Table 3 shows the number average molecular weight of the obtained urethane resin and the ratio (%) of the liquid epoxy resin to the total mass of the urethane resin and the liquid epoxy resin.

[0164] (Comparative Production Example 4)

[0165] A composition containing only the liquid epoxy resin described in Table 3 was referred to as composition (U-4).

[0166] (Comparative Production Example 5)

[0167] In a reaction container equipped with a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device, 0.7 parts of 1-thioglycerol as a chain transfer agent having a mercapto group, 2.0 parts of glycidyl methacrylate as an ethylenically unsaturated monomer having one or more epoxy groups in the molecule, 17.1 parts of n-butyl methacrylate as another ethylenically unsaturated monomer, and 50% of methyl ethyl ketone based on the total mass of the monomers were first added, and the temperature was raised to 75° C. under a nitrogen atmosphere. 2,2'-azobis(2'4-dimethylvaleronitrile) as a polymerization initiator was added thereto in an amount of 0.7% based on the total mass of the chain transfer agent and the ethylenically unsaturated monomers at 1 hour intervals for seven times, and the reaction was continued for 2 hours after the addition of the polymerization initiator to obtain an acrylic polyol. Next, a reaction vessel different from the previous one equipped with a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device was charged with 18.4 parts of P-2000 as a polyol, 1.6 parts of isophorone diisocyanate as a diisocyanate, 0.01% of butyltin dilaurate as a catalyst relative to the total mass of the polyol and the diisocyanate, and 50% of methyl ethyl ketone relative to the total mass of the monomers, and stirred uniformly, and then heated at 90°C for 30 minutes under a nitrogen atmosphere to obtain a urethane resin. The end point of the reaction was determined by the peak derived from the isocyanate group (2270 cm-1) according to FT-IR. -1 The previous acrylic polyol and urethane resin were mixed, 60 parts of jER828 as a liquid epoxy resin were added, and after uniform stirring, methyl ethyl ketone was removed under reduced pressure to obtain a mixture (U-5) of acrylic polyol, urethane resin, and liquid epoxy resin. The number average molecular weight of the obtained acrylic polyol and urethane resin, the ratio (%) of monomers having epoxy groups in the acrylic polyol, and the ratio (%) of the liquid epoxy resin relative to the total mass of the acrylic polyol, urethane resin, and liquid epoxy resin are shown in Table 3.

[0168] (Comparative Production Example 6)

[0169] Comparative Production Example 6 was synthesized as follows based on the method for producing a polyurethane-modified epoxy resin described in Japanese Patent Application Laid-Open No. 2017-2130.

[0170] In a reaction vessel equipped with a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device, 87 parts by mass of polycaprolactone diol ["Placcel 230" manufactured by Daicel Co., Ltd., weight average molecular weight (Mw) 3,000] and 13 parts by mass of isophorone diisocyanate were mixed, and 0.1 parts by mass of a dioctyltin catalyst ("Neostann U-820" manufactured by Nitto Kasei Co., Ltd.) was added as a catalyst, and the mixture was reacted at 70° C. for 3 hours to obtain an isocyanate group-containing urethane resin. The isocyanate group content of the isocyanate group-containing urethane resin was 2.4% by mass. Then, in another reaction container including a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device, 30 parts by mass of a carbamate resin containing an isocyanate group and 70 parts by mass of a bisphenol A type epoxy resin ("Epiclon 850" manufactured by DIC Corporation, epoxy equivalent 188 g / eq, hydroxyl value 20 mgKOH / g) were mixed, and the temperature was raised to 70°C to obtain a polyurethane modified epoxy resin (U-6). The end point of the reaction was determined by the peak derived from the isocyanate group (2270 cm-1) of FT-IR. -1 The epoxy equivalent of the obtained polyurethane-modified epoxy resin (U-6) was 255 g / eq.

[0171] [Table 4]

[0172] Table 4

[0173]

[0174] <Production Example of Hardener>

[0175] (Manufacturing Example 1)

[0176] In a reaction vessel including a nitrogen inlet pipe, a stirrer, a thermometer, and a reflux device, 15.8 parts of D-400, 73.4 parts of D-2000, and 208 parts of isopropanol were placed, and the mixture was uniformly stirred at 40° C. under a nitrogen atmosphere. A mixed solution containing 10.9 parts of isophorone diisocyanate and 35.2 parts of ethyl acetate was added dropwise over 30 minutes, and the mixture was stirred and reacted for 1 hour to obtain a urea compound solution. The obtained urea compound solution was desolvated under reduced pressure to obtain a urea compound (UR-1). The end point of the reaction was determined by the peak derived from the isocyanate group (2270 cm-1) according to FT-IR. -1 The number average molecular weight of the obtained urea compound (UR-1) was 3100, and the amine value was 27.4 mgKOH / g.

[0177] (Production Example II)

[0178] In a dropping container including a nitrogen inlet pipe, a stirring device, a thermometer, and a reflux device, 46.6 parts of P-2000, 22.7 parts of C-1090, 20.2 parts of isophorone diisocyanate, and 0.01% of butyltin dilaurate as a catalyst relative to the total mass of the polyol and the diisocyanate were placed, and after uniform stirring, an isocyanate-terminated prepolymer was synthesized at 90° C. for 30 minutes under a nitrogen atmosphere at 90° C. for 4 hours, and then 51.1 parts of ethyl acetate were added to prepare an isocyanate-terminated prepolymer solution. Subsequently, 10.5 parts of hexamethylenediamine and 48.9 parts of isopropanol were placed, and the isocyanate-terminated prepolymer solution was dropped over 30 minutes while uniformly stirring at 40° C. under a nitrogen atmosphere, and then stirred for 1 hour to obtain a urea compound solution. The obtained urea compound solution was desolvated under reduced pressure to obtain a urea compound (UR-2). The end point of the reaction was determined by the peak derived from the isocyanate group (2270 cm -1 The number average molecular weight of the obtained urea compound (UR-2) was 3900, and the amine value was 50.9 mgKOH / g.

[0179] (Production Example III)

[0180] The polyolefin having an amino group is synthesized as follows based on the Gabriel reaction which has been known for a long time. In a reaction vessel including a nitrogen inlet tube, a stirrer, a thermometer, and a reflux device, 77.3 parts of Krasol LBH-P3000, 14.9 parts of p-toluenesulfonyl chloride, 7.9 parts of pyridine, and 100 parts of chloroform are placed, and stirred at room temperature under a nitrogen atmosphere to react for 6 hours. After the reaction, 200 mL of a 1M hydrochloric acid aqueous solution is added to make it acidic, and then extracted with chloroform, and the organic layer is separated and dried to obtain toluenesulfonated polybutadiene. Subsequently, 81.3 parts of the obtained toluenesulfonated polybutadiene, 21.7 parts of potassium phthalimide, and 80 parts of N,N-dimethylformamide are placed in the reaction vessel, and refluxed at 140°C for 8 hours under a nitrogen atmosphere. An aqueous ammonium chloride solution was added to the reaction solution for neutralization, and the solution was extracted with hexane, and the organic layer was separated and dried to obtain phthalimidized polybutadiene. Subsequently, 42.0 parts of the obtained phthalimidized polybutadiene, 6.75 parts of hydrazine monohydrate, and 50 parts of ethanol were placed in a reaction container, and stirred at room temperature under a nitrogen atmosphere for 2 hours. After the reaction, the solution was made alkaline with an aqueous sodium hydroxide solution, and then extracted with hexane, and the organic layer was separated and dried to obtain a polyolefin compound (UR-3) having an amino group. The number average molecular weight of the obtained polyolefin compound (UR-3) was 3000, and the amine value was 34.0 mgKOH / g.

[0181] [Table 5]

[0182] Table 5

[0183]

[0184] <Preparation of Adhesive Resin Composition>

[0185] [Example 1]

[0186] 10 parts of the composition (DE-1) containing the comb-type urethane-acrylic composite resin (D-1) and the liquid epoxy resin (E) obtained in Production Example 1, 3.1 parts of D-400 as a hardener (F), and 0.1 parts of triethylenetetramine were stirred and mixed at room temperature to prepare an adhesive resin composition of Example 1.

[0187] [Example 2 to Example 32 and Comparative Example 1 to Comparative Example 4]

[0188] The same operation as in Example 1 was carried out except that the formulation compositions were changed to those shown in Tables 6 to 9, to prepare adhesive resin compositions of Examples 2 to 32 and Comparative Examples 1 to 6.

[0189] <Evaluation 1 of Adhesive Resin Composition>

[0190] The following tests were performed on the adhesive resin compositions prepared in Examples and Comparative Examples. The evaluation results are shown in Tables 6 to 9.

[0191]

[0192]

[0193]

[0194] [Table 9]

[0195] Table 9

[0196]

[0197] [Appearance]

[0198] Each adhesive resin composition was filled in a sheet mold having a thickness of 2 mm, the surface was leveled, and the mold was cured at 25° C. for 7 days to obtain a test piece, which was then evaluated according to the following evaluation criteria at a temperature of 25° C. and a relative humidity of 50%.

[0199] (Evaluation Criteria)

[0200] ++: Visually transparent and without phase separation. (Good)

[0201] +: Slightly opaque or slightly phase separated can be visually observed. (Can be used)

[0202] NG: Clearly opaque or obvious phase separation can be observed visually. (Unusable)

[0203] [Shear Adhesion]

[0204] Each adhesive resin composition was applied to a carbon fiber reinforced plastic substrate (length 100 mm, width 25 mm, thickness 2 mm) in a manner of 10 mm in length, 25 mm in width, and 0.1 mm in thickness, and laminated to the carbon fiber reinforced plastic substrate, and cured at 25°C for 7 days while being pressed to maintain a thickness of 0.1 mm to obtain a test piece. The obtained test piece was measured for shear adhesion using a tensile tester at a tensile speed of 1 mm / min under the conditions of a temperature of 25°C and a relative humidity of 50%, and judged according to the following evaluation criteria.

[0205] (Evaluation Criteria)

[0206] +++: Shear adhesion is 20 MPa or more. (Very good)

[0207] ++: Shear adhesion is 15 MPa or more and less than 20 MPa. (Good)

[0208] +: Shear adhesion is 10 MPa or more and less than 15 MPa. (Can be used)

[0209] NG: Shear adhesion is less than 10MPa. (Cannot be used)

[0210] [Breaking stress, breaking elongation]

[0211] Each resin composition adhesive was filled in a sheet mold frame with a thickness of 2 mm, the surface was flattened, and after being cured at 25° C. for 7 days, it was punched out using a No. 3 dumbbell mold to produce a dumbbell-shaped test piece for evaluation. Using the dumbbell-shaped test piece, a tensile test was performed at a temperature of 25° C. and a relative humidity of 50% at a tensile speed of 50 mm / min, and the breaking stress (MPa) and the breaking elongation (%) were measured and judged according to the following criteria.

[0212] (Evaluation criteria for fracture stress)

[0213] +++: The breaking stress is 20 MPa or more. (Very good)

[0214] ++: The breaking stress is 15 MPa or more and less than 20 MPa. (Good)

[0215] +: The breaking stress is 10 MPa or more and less than 15 MPa. (Can be used)

[0216] NG: The breaking stress is less than 10MPa. (Cannot be used)

[0217] (Evaluation criteria for elongation at break)

[0218] +++: Elongation at break is 100% or more. (Very good)

[0219] ++: Elongation at break is 80% or more and less than 100%. (Good)

[0220] +: Elongation at break is 60% or more and less than 80%. (Can be used)

[0221] NG: Elongation at break is less than 60%. (Cannot be used)

[0222] [Impact resistance]

[0223] Each adhesive resin composition was applied to a stainless steel substrate (length 100 mm, width 25 mm, thickness 2 mm) in a manner of 10 mm in length, 25 mm in width, and 0.1 mm in thickness, and then bonded to the stainless steel substrate. The test piece was cured at 25°C for 7 days while being crimped to maintain a thickness of 0.1 mm to obtain a test piece. Under the conditions of a temperature of 25°C and a relative humidity of 50%, the number of times the test piece obtained was broken due to the DuPont impact test was measured and judged according to the following criteria. The DuPont impact test was performed using an impact mold with a 1 / 2 inch roundness at the front end, and a 500 g weight was allowed to fall freely from a height of 5 cm.

[0224] (Evaluation Criteria)

[0225] +++: No breakage after 10 tests. (Very good)

[0226] ++: Broken at the 5th to 9th time. (Good)

[0227] +: Broken at 2nd to 4th time. (Can be used)

[0228] NG: At the first break. (Unusable)

[0229] <Evaluation 2 of Adhesive Resin Composition>

[0230] The adhesive resin compositions prepared in Examples and Comparative Examples were subjected to the same test as in Evaluation 1 except that the curing conditions were changed to 80° C. and 1 day. The evaluation results are shown in Tables 5 to 7.

[0231] <Overall Evaluation>

[0232] The adhesive resin compositions prepared in the examples and comparative examples were comprehensively evaluated according to the following criteria. The evaluation results are shown in Tables 6 to 9.

[0233] (Comprehensive evaluation criteria)

[0234] ++: All test items in evaluation 1 and evaluation 2 were judged as ++ or above and there was no difference in the evaluation results. (Good)

[0235] +: All test items in Evaluation 1 and Evaluation 2 were judged as ++ or above, but there were differences in the evaluation results; or, in any of the evaluation items in Evaluation 1 and Evaluation 2, regardless of the difference in the evaluation results, there was no NG judgment but there was a + judgment.

[0236] (Available)

[0237] NG: In any of the evaluation items of Evaluation 1 and Evaluation 2, the result is NG or below. (Cannot be used)

[0238] The adhesive resin composition of the present invention obtained good results in adhesion, impact resistance, breaking stress, and breaking elongation. On the other hand, the adhesive resin composition of the comparative example had some or all of the adhesion, breaking stress, and breaking elongation that were inferior to those of the examples.

[0239] This application claims priority based on Japanese patent application No. 2022-130011 filed on August 17, 2022, and Japanese patent application No. 2023-026828 filed on February 24, 2023, and all the disclosed contents are incorporated into this application.

Claims

1. An adhesive resin composition comprising: A comb-type urethane-acrylic composite resin (D) having residues derived from an acrylic polyol (A) containing an epoxy group in the molecule and having a hydroxyl group at one end, a polyol (B) (except the acrylic polyol (A)), and a diisocyanate (C); Liquid epoxy resin (E); and Hardener (F).

2. The adhesive resin composition according to claim 1, characterized in that The liquid epoxy resin (E) has two or more epoxy groups in the molecule.

3. The adhesive resin composition according to claim 1, characterized in that The acrylic polyol (A) is contained in an amount of 5 to 80% by mass in 100% by mass of the comb-type urethane-acrylic composite resin (D).

4. The adhesive resin composition according to claim 1, characterized in that The acrylic polyol (A) contains 5% by mass or more and less than 100% by mass of an ethylenically unsaturated monomer (a-1) having one or more epoxy groups in the molecule, based on 100% by mass.

5. The adhesive resin composition according to claim 1, characterized in that The liquid epoxy resin (E) is contained in an amount of 20% to 80% by mass in 100% by mass of the total of the comb-shaped urethane-acrylic composite resin (D) and the liquid epoxy resin (E). 6 . A cured product comprising the adhesive resin composition according to claim 1 .

7. A laminate comprising a layer comprising the cured product according to claim 6 on a substrate.

Citation Information

Patent Citations

  • High molecular weight epoxy resin, epoxy resin composition and cured product

    JP2015063595A

  • Laminate in which different kinds of members are bonded with curable resin composition

    JP2015182248A

  • Polyurethane modified epoxy resin and adhesive

    JP2017002130A

  • Epoxy resin composition

    JP2018002766A

  • Muffler for engine, air-cooled engine and work machine

    JP2022130011A